Is there a demand for multi-year crop insurance? - Maria Osipenko; Zhiwei Shen; Martin Odening (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
In this paper we adapt a dynamic discrete choice model to examine the aggregated demand for single- and multi-year crop insurance contracts. We show that in a competitive insurance market with heterogeneous risk averse farmers, there is simultaneous demand for both insurance contracts. Moreover, the introduction of multi-year contracts enhances the market penetration of insurance products. Using U.S. corn yield data, we empirically assess the potential of multi-year crop insurance.
Keywords: D81; G22; Q14; 330; multi-year insurance; index-based crop insurance; dynamic discrete choice model